Cywilnoprawne znaczenie przebaczenia: [Civil law meaning of forgiveness] (Studia Prawnicze / The Legal Studies, 2013)
Nie będzie, jak sądzę, przesadą postawienie na wstępie tego artykułu tezy, że na gruncie prawa polskiego przebaczeniu – jako zjawisku w pierwszym rzędzie etycznemu – przypisana została dość duża doniosłość prawna. Po pierwsze, stosownie do art. 899 § 1 kc darowizna nie może być z powodu rażącej niewdzięczności odwołana, jeżeli darczyńca przebaczył obdarowanemu. Po drugie, w myśl art. 930 § 1 kc spadkobierca nie może być uznany za niegodnego, jeżeli spadkodawca mu przebaczył. Po trzecie, zgodnie z art. 1010 § 1 kc spadkodawca nie może wydziedziczyć uprawnionego do zachowku, jeżeli mu przebaczył. Biorąc pod uwagę wymienione regulacje, z łatwością można zauważyć, że podstawowe prawne znaczenie przebaczenia sprowadza się do usunięcia możliwości zastosowania przez podmiot uprawniony szczególnego rodzaju sankcji w stosunku do osoby, która postąpiła względem niego nieetycznie: po dokonanym przebaczeniu darczyńca – mimo rażącej niewdzięczności obdarowanego – nie może już odwołać darowizny, spadkodawca – mimo jawnie nagannego postępowania spadkobiercy – nie może pozbawić go prawa do zachowku, a zgłoszone przez osoby uprawnione żądanie uznania spadkobiercy za niegodnego nie zostanie przez sąd uwzględnione. In contemporary civilistic literature a lot of space is devoted to the legal character of forgiveness. In the article I join the opinion that forgiveness is not the legal activity, but it also does not constitute a purely internal emotional act, but is the externalized, perceptible for the third parties manifestation of this state. The main subject of my interest is, however, the issue of the legal meaning of forgiveness, that is legal steps, which were assigned by the legislator. They are based on the fact that after the forgiveness is made, you can no longer cancel the donation, the testator cannon disinherit the heir, and the court cannot consider the heir as unworthy. In this article I pose and justify the thesis that these are too far-reaching consequences, because I think that despite the forgiveness which was made, the donor should maintain the right to cancel the donation, and the testator to make the disinheritance. I believe that forgiveness is one thing, and resignation from applying the sanction punishment) – the other; the first one does not have to entail the other. This may also be proven by the view of Seneca mentioned by me, who stated that it would be contradictory with the nature of the stoic sage to pardon the deserved punishment – such understood forgiveness is contrary to the justice and it denies its essence.